Total plasma cholesterol profile in superovulated crossbred cattle - SHARMA, UTSAV; MAURYA, S N; KUMAR, SURESH; RAWAT, A K (The Indian Journal of Animal Reproduction, 2007)
Crossbred cows (n = 24) were divided in to 4 groups. The animal of each group were treated on day7 (day O= day of estrous) with different hormonal preparation viz 500 I.U. hCG (Group 1), 5 mgEs/radio/ valerate (Group II), IO ig GnRH (Group III) l}nd 1 ml NSS (Group IV). Animal in eachgroup were superovulated on day 10 of estrous cycle with FSH-P. The superovulatory response wasdetermined by counting corpora lutea present on both the ovaries. Total cholesterol level increasedsignificantly (P0.05) in group III. Positive (P < 0.0 I) correlation existed between ovulation rate and total cholesterolon day 4. This correlation was also significant (P
Keywords: Cholesterol; Superovulation; Cattle